2013
DOI: 10.1016/j.devcel.2013.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Adult Duct-Lining Cells Can Reprogram into β-like Cells Able to Counter Repeated Cycles of Toxin-Induced Diabetes

Abstract: It was recently demonstrated that embryonic glucagon-producing cells in the pancreas can regenerate and convert into insulin-producing β-like cells through the constitutive/ectopic expression of the Pax4 gene. However, whether α cells in adult mice display the same plasticity is unknown. Similarly, the mechanisms underlying such reprogramming remain unclear. We now demonstrate that the misexpression of Pax4 in glucagon(+) cells age-independently induces their conversion into β-like cells and their glucagon sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
196
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 182 publications
(209 citation statements)
references
References 35 publications
9
196
1
3
Order By: Relevance
“…Al-Hasani et al [65] recently reported that upon Pax4 misexpression, adult alpha cells are converted into insulinproducing cells, independent of their age, mutation state or microenvironment. They also report a duct cell to beta-like cell regeneration pathway that could be repeatedly activated by streptozotocin injury in an age-dependent manner.…”
Section: Adulthoodmentioning
confidence: 99%
“…Al-Hasani et al [65] recently reported that upon Pax4 misexpression, adult alpha cells are converted into insulinproducing cells, independent of their age, mutation state or microenvironment. They also report a duct cell to beta-like cell regeneration pathway that could be repeatedly activated by streptozotocin injury in an age-dependent manner.…”
Section: Adulthoodmentioning
confidence: 99%
“…Néanmoins, les relations de lignage entre précurseurs canalaires, cellules exprimant Neurog3 et cellules endocrines restent floues et controversées [15,24] (➜). Après avoir confirmé par immunomarquage la réex-pression de Neurog3 dans les cellules canalaires des animaux transgé-niques exprimant Pax4 dans les cellules , nous avons croisé ces souris avec un autre modèle transgénique, ce qui nous a permis d'observer le devenir de ces cellules canalaires [26]. Nos résultats démontrent que les cellules qui réactivent Neurog3 adoptent un destin endocrine, et SYNTHÈSE REVUES rentes combinaisons de facteurs de transcription (Neurog3, Pdx1 et MafA [musculoaponeurotic fibrosarcoma oncogene homolog A)]) permet la conversion des cellules acinaires infectées en cellules -like chez la souris adulte.…”
Section: Les Canaux Pancréatiques : Une Source Potentielle De Précursunclassified
“…We therefore generated animals allowing the forced expression of Pax4 in a-cells and animals permitting the specific loss of Arx expression in a-cells. [3][4][5] In both instances, a conversion of a-cells into b-like cells was indeed observed. Surprisingly, we also outlined continued processes of compensatory a-cell neogenesis, such cells being again turned into b-like cells upon Pax4 misexpression/Arx inactivation.…”
mentioning
confidence: 74%
“…Importantly, the b-like cells thereby generated were found to be functional and able to replace their endogenous counterparts in vivo. [3][4][5] Lastly, further worked provided evidences that the main trigger of the conversion of a-cells into b-like cells (and the ensuing cycle of b-like cell neogenesis) was the downregulation of Arx activity, Pax4 misexpression mainly acting to decrease Arx expression. 5 Even though promising, these results remained far from a putative medical application.…”
mentioning
confidence: 99%